SOCIOECONOMIC DEVELOPMENT OF GORNY BADAKHSHAN - KHONALIEV, Nazarali (CENTRAL ASIA AND THE CAUCASUS, 2004)
In January 2005, the Gorno-Badakhshan Autonomous Region (GBAO) will mark its 80th an-anniversary as part of the Republic of Tajikistan: In historical terms it is not much—measured by in-dividual lives, however, it is a lot. In the distant past the Western Pamir (Shugnan, Rushan, Wahan,Garan and Ishkashim) consisted of small independent possessions ruled by hereditary potentate's until in the mid-19th century the geopolitical interests of the British and Russian empires clashed in Central Asia. In 1873, they signed an agreement on the West Pamirian borders under which Shugnan,Rushan, and Wahan were excluded from the sphere of influence of the Afghan emirate. In 1883, Afghan Emir Abdurahman Khan captured the western regions in violation of the earlier treaty on the inviolability of the borders along the River Panj. Russia had to use force to recapture its control over the territory.